Pengaruh Partisipasi Anggaran, dan Kejelasan Sasaran Anggaran Terhadap Kinerja Manajerial Dengan Komitmen Organisasi Sebagai Pemediasi (Studi kasus pada Pemerintah Daerah di Jawa Tengah) - Siswo Nugroho, Prihasantyo; Turmudhi, Anis; Prasetya, Adhitya Yoga (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2021)
The aim of this study is to analyze: 1) the influence of budgetary participation on organizational commitment; 2) the influence of clarity of budget targets on organizational commitment; 3) the influence of budget participation on managerial performance; 4) the influence of clarity of budget targets on managerial performance; 5) The influence of organizational commitment on managerial performance. The population used in this study is the Regional Work Unit (Satuan Kerja Perangkat Daerah) of Central Java Province, while the sample in this study is the section head, subdivision head, and department head involved in budgeting in each SKPD of Central Java Province. The results of this study are 1) budget participation has a positive effect on organizational commitment; 2) clarity of budget targets does not affect organizational commitment; 3) budget participation has a positive effect on managerial performance; 4) clarity of budget targets has a positive effect on managerial performance; 5) organizational commitment has no effect on managerial performance.